PRODUKTIVITAS PERIKANAN PURSE SEINE BERDASARKAN MUSIM PENANGKAPAN DI PULAU AMBON - Polhaupessy, Rosihan (Program Studi Pendidikan Biologi FKIP Unpatti, 2020)
Background: The difference between ship dimensions (size, GT and PK of the ship) and the size of fishing devices, as well as the number of days of purse saine operation due to the effect of the season in Ambon Island is suspected as the significant problems which are affecting the productivity of fishing devices, besides that the season is also affecting the fishermen’s income because of the difference in the selling prices between the seasons of East and West. This research aims to know the productivity of the business of Purse Sein in Ambon Island. Method: The method of analysis used is the productivity of fishing vessels according to the regulation of the Minister of Maritime and Fisheries number 86, 2016. Result: The result of the research, it is concluded that the productivity of fishing purse seine in Ambon Island showed that the highest productivity/trip of fishing in the fish season amounted to 638 kg/trip and the season less fish amounted to 288.6 kg/trip, while the productivity/number of crew in the fish season is 36.1 kg/crew and the season less fish is 16.6 kg/crew. Conclusion: Productivity of fishing purse seine in Ambon Island is not determined entirely by the use of adequate facilities and infrastructure; it means that the rationalization of the use of facilities and infrastructure should be proportional to the increase in production, because not always the use of facilities and infrastructures in high quantities can produce high production.